Parents' self-efficacy and the quality of supervised driving practice they provide for their children. (May 2022) - Rodwell, David; Bates, Lyndel; Larue, Grégoire S.; Watson, Barry; Haworth, Narelle
Highlights: Parents' driving self-efficacy is associated with quality of supervised practice. General parental self-efficacy did not predict quality of supervised practice. Mothers reported providing higher quality supervised practice than fathers. Abstract: Learner drivers must gain supervised driving practice in a wide variety of driving situations to prepare them for independent driving. This study investigated the way that sociodemographic factors, parental self-efficacy and driving self-efficacy of parents are associated with the quality of supervised driving practice they provide to their learner driver children. An online survey was completed by 293 fully licensed parents (female = 86%) of learner (52%) and provisional (intermediate; 48%) drivers from Queensland, Australia. A variable indicating quality of supervised practice was defined based on the understanding that higher frequency and greater variety of driving situations and environments represents higher quality supervised practice. Hierarchical multiple regression was used to analyse parent responses. As predicted, driving self-efficacy was significantly and positively associated with quality of supervised practice. However, no significant association was found between parental self-efficacy and quality of supervised practice. Parent gender and perceived level of involvement were also important predictors of supervised practice quality. The association between previous experience with providing supervised practice and supervised practice quality was unclear. A key implication of this research is that devising methods to improve the driving self-efficacy of parents may contribute to provision of more frequent and varied supervised practice.